2006
DOI: 10.21273/horttech.16.2.0277
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Assessment of the Impact of Current Flooding Practices on Nonstructural Carbohydrate Concentrations of Cranberry

Abstract: ADDITIONAL INDEX WORDS. Vaccinium macrocarpon, respiration, temperature SUMMARY. American cranberry (Vaccinium macrocarpon) production sites are often fl ooded for pest control and crop harvest. However, little is known about how this practice affects vines. A survey was conducted in Massachusetts over a 3-year period to determine the effect of spring, fall, and winter fl oods on total nonstructural carbohydrate concentration (TNSC) of cranberry uprights of four cultivars. With a few exceptions, TNSC generally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…This suggests that the seedlings were adapting to drought first by investing more carbon in belowground tissues to maximize water capture and that investment in roots is maintained preferentially even under severe drought stress (Ext). Investment in roots was also proportionally greater than investment in leaves under waterlogged conditions, although in this case, the reason is presumably to maximize oxygen uptake [47,48]. The overall reduction in biomass under drought and waterlogging conditions is consistent with previous studies [49][50][51] that showed similar changes in roots compared to aboveground biomass.…”
Section: Discussionsupporting
confidence: 87%
“…This suggests that the seedlings were adapting to drought first by investing more carbon in belowground tissues to maximize water capture and that investment in roots is maintained preferentially even under severe drought stress (Ext). Investment in roots was also proportionally greater than investment in leaves under waterlogged conditions, although in this case, the reason is presumably to maximize oxygen uptake [47,48]. The overall reduction in biomass under drought and waterlogging conditions is consistent with previous studies [49][50][51] that showed similar changes in roots compared to aboveground biomass.…”
Section: Discussionsupporting
confidence: 87%
“…A 42% decline in NSC was found following early-fall floods of 3 to 27 days in American cranberry (Vaccinium macrocarpon Ait. ; Botelho and van Heuvel 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Shorter retrieval intervals were used in the latter case since the risk of injury for flooded vines is higher under summer conditions 19,25 . To simulate spring conditions in Massachusetts, three water temperatures (10, 15 and 20 C) were evaluated.…”
Section: Water Temperature and Flood Duration Studiesmentioning
confidence: 99%
“…16,17 . Temperature is an important criterion as water that is too warm can negatively impact stored carbohydrates in cranberry and reduce yields 19 . Temperature is an important criterion as water that is too warm can negatively impact stored carbohydrates in cranberry and reduce yields 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation